EFFECT OF THE USE OF TUTORIAL METHODS ON LIVELINESS OF STUDENTS IN MIDWIFERY ON ASKEB I IN AKBID NYAI AHMAD DAHLAN YOGYAKARTA - Stefi Fivtri Lestari De Flores (Jurnal EduHealth, 2020)
One form of learning process with Competency-Based Curriculum system (KBK) is to use tutorial methods. The role of student learning is essentially in a tutorial is a group discussion process that requires management skills. The success of the tutorial discussion will be greatly influenced by the stages of the structure that must be undertaken by students called the Seven Jump methode. This research aims to find outthe influence of the use of tutorial methods(seven jump) on the activeness of studying students of the second semester of midwifery at the Midwifery Care I course at the Academy of Midwifery Nyai Ahmad Dahlan Yogyakarta in 2013. This study uses quasi design experiments. Use non-equivalent control groupdesign. The sample in the study numbered 37 people with a division of 15 samples as an experimental group and 22 samples as a control group. Data analysis uses frequency distribution and bivariate analysis using wilcoxon match paired test statistics. Based on the research conducted, there was a significant increase in the activeness of students studying in the second semester of MIDWIFERY AT OBSTETRICS I Pre and Post Test In The Experimental Group p = 0.001 < 0.05. The increase before and after the intervention was 18.73. There was no significant increase in the activeness of study of second semester students of MIDWIFERY AT midwifery in the Midwifery Care Course I Pre and Post Test In The Control Group p = 0.928 > 0.05. The difference before and after the intervention was 0.04. The advice from researchers is expected to improve the quality of learning about Midwifery Care I by using a variety of learning media, so that students better understand Midwifery Care I.